Suidae from Kanapoi. Issue 140 (March 2020) - Geraads, Denis; Bobe, René
Abstract: The whole collection of Suidae from Kanapoi is revised in the context of the systematics and evolution of Nyanzachoerus in the Pliocene of Eastern Africa. It contains only two species, Nyanzachoerus kanamensis and Notochoerus jaegeri . The size and morphology of their premolars overlap, but not those of their m3s. No transitional form between them is known in Kenya, but some populations from Uganda and Ethiopia display intermediate characters, suggesting that No. jaegeri could be descended from a kanamensis -like ancestor. However, the cranial remains of No. jaegeri from Kanapoi are insufficient to formally establish the affinities of the species. On the basis of the dentition, Notochoerus euilus could be descended from No. jaegeri . The noticeable absence of Kolpochoerus at Kanapoi (and in the whole Turkana Basin at that time) remains unexplained. The presence of a species with affinity to Nyanzachoerus tulotos at Ekora raises the possibility that uppermost Miocene sediments occur there.